Causal attributions of success and failure and mood states in football players - Szczepaniak, J.; Guszkowska, M. (Polish Journal of Sport and Tourism, 2016)
Introduction. The aim of the study was to determine the causal attributions of success and failure in a football match in a group of football players, as well as to investigate the association of the players` attributions with their level of achievement and the relationships between their causal attributions and affective states. Material and methods. The study involved 75 football players, including 44 players from the first league and 31 players from the third league. The research was carried out using the Profile of Mood States (POMS) by D.M. McNair, M. Lorr, and L.F. Droppleman and a specially designed questionnaire concerning the causal attributions of success and failure. Results. It was found that the football players who participated in the study tended to attribute success to internal causes and failure to external causes. More frequent use of external attributions most likely had an adverse impact on the mood state of the players. Conclusion. Information concerning the attributions that a given player makes can be useful for coaches, as it can help them develop the athlete`s mental abilities more effectively. Beliefs related to attributions can be modified. It is worth considering the benefits of encouraging internal attributions in the case of success and external attributions in situations of failure.